2017
DOI: 10.1136/bjophthalmol-2016-310077
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intraocular pressure, corneal thickness and corneal biomechanics after congenital cataract surgery

Abstract: IOP, CCT, CH and IOP were significantly different in treated eyes compared with normal eyes after congenital cataract surgery. These variables were primarily affected by the type of surgery. Primary intraocular lens implantation preserved corneal structure and function of the anterior chamber angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In the studies undergone until present, significant differences have been observed between the biomechanical corneal values pre- and post-surgery. The CH value has decreased in the immediate post-surgically period and went back to the pre-surgically level in 1-2 weeks; no statistically significant change has been identified in the CRF values [ 42 - 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies undergone until present, significant differences have been observed between the biomechanical corneal values pre- and post-surgery. The CH value has decreased in the immediate post-surgically period and went back to the pre-surgically level in 1-2 weeks; no statistically significant change has been identified in the CRF values [ 42 - 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another school of thought for risk of developing glaucoma being more in aphakic group rather than in primary pseudophakia group is due to the exposure of the maturing angle structures and maturing cornea to harmful side effects of vitreous components. 8 This access to trabecular meshwork and cornea is less if artificial lens is implanted at the same time as that of cataractous lens extraction. So, increased CCT in aphakia and pseudophakia eyes following congenital cataract extraction and its effect on IOP measurement should be borne in mind before making a diagnosis of glaucoma and prescribing anti-glaucoma medications in children.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Several previous studies have demonstrated that corneal thickness and biomechanics change after congenital cataract surgery. Faramarzi et al 11 recently demonstrated that CCT increased and corneal hysteresis (CH) decreased after congenital cataract surgery without intraocular lens (IOL) implantation, whereas primary IOL implantation preserved corneal thickness and biomechanics. 11 Muir et al 12 found that CCT increased after congenital cataract surgery and mean CCT was greater in aphakic eyes than in pseudophakic eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Faramarzi et al 11 recently demonstrated that CCT increased and corneal hysteresis (CH) decreased after congenital cataract surgery without intraocular lens (IOL) implantation, whereas primary IOL implantation preserved corneal thickness and biomechanics. 11 Muir et al 12 found that CCT increased after congenital cataract surgery and mean CCT was greater in aphakic eyes than in pseudophakic eyes. Simsek et al 13 reported a significant difference in CCT between aphakic eyes and pseudophakic eyes in which an IOL was implanted at the time of congenital cataract surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation